2017
DOI: 10.1136/neurintsurg-2016-012946
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular flow diversion for treatment of anterior communicating artery region cerebral aneurysms: a single-center cohort of 50 cases

Abstract: The PED can be used safely and effectively in the treatment of aneurysms of the ACoA region. This represents a good alternative treatment option to microsurgical clipping and endovascular coiling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 33 publications
6
34
0
Order By: Relevance
“…We report an occlusion rate of 37.5% at first DSA control, rising to 91.7% at long-term follow-up (i.e., with > 2 DSA controls). This slow pattern of occlusion is described in other studies 8,14 with high occlusion rates (> 80% at long-term follow-up), suggesting that occlusion could be a matter of time. The mean time of occlusion was 11.6 months, with a wide range from 3 to 27 months.…”
Section: Occlusion Rate Sac Reabsorption and Recurrencesupporting
confidence: 78%
See 2 more Smart Citations
“…We report an occlusion rate of 37.5% at first DSA control, rising to 91.7% at long-term follow-up (i.e., with > 2 DSA controls). This slow pattern of occlusion is described in other studies 8,14 with high occlusion rates (> 80% at long-term follow-up), suggesting that occlusion could be a matter of time. The mean time of occlusion was 11.6 months, with a wide range from 3 to 27 months.…”
Section: Occlusion Rate Sac Reabsorption and Recurrencesupporting
confidence: 78%
“…Several endovascular techniques, such as stent-assisted coiling, 28 balloon remodeling, 9 Y stenting with or without coiling, 24 and Woven EndoBridge (WEB) device, 20 have been used for the treatment of bifurcation aneurysms, but results remain suboptimal with significant recurrence and complication rates. Several reports have demonstrated that the treatment of these types of aneurysms is feasible and safe, 8,10,12,14,19,21,23,29 whereas others have shown morbidity and mortality rates rising up to 21% and 10%, respectively. 4,26 The most common complications are periprocedural thrombus formations, arterial branch perforation, in-stent thrombosis, side-branch occlusion, and perforator strokes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early use of flow diversion was centered on the treatment of aneurysms arising from the internal carotid artery (ICA) with 79/108 (73.1%) aneurysms treated in the PUFS study arising from either the cavernous or ophthalmic segments of the ICA and the majority of the aneurysms being between 10 and 25 mm in size (78.7%). Since the publication of this K p48MW pivotal trial, numerous reports on the use of flow diversion distal to the circle of Willis have been published [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Ravindran et al [26] recently reported their multicohort study of FDS use distal to the circle of Willis defined as at or beyond the A1, M1 and P1 segments of the ACA, MCA and PCA, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, both in the United States and, more commonly, abroad, the PED and other flow diverters (FDs) are being used to treat more distal aneurysms, including those affecting the MCA bifurcation, 7 anterior communicating artery, 8 posterior communicating artery (PcomA) segments (including in the setting of "fetal PcomA" 9 ), distal anterior cerebral artery, 10 and others. 6,11,12 While reasons for these trends are complex and multifactorial, published results have been generally encouraging, 7,8,11,12 with a few groups reporting a high burden of ischemic complications. 13,14 The mechanisms responsible for efficiency of flow diversion in aneurysm treatment have been well-described.…”
mentioning
confidence: 99%